Solving river blindness disease in terms of progression by using SIR / Mohd Rahimie Md Noor... [et al.] - Md Noor, Mohd Rahimie; Hamiri, Siti Khadijah; Anak Langgar@Jimun, Donna; Syed Adnan, Sharifah Athirah; Nafi, Mohd Noor Azam; Mohamad, Roslim (Universiti Teknologi MARA Cawangan Pulau Pinang, 2018)
River blindness disease has become a major problem in Northern Nigeria, Africa especially in a rural agricultural land located to a nearby river edge. The population is at a higher risk of being infected for being very close to the breeding site of black fly or known as Simulium damnosum. The infected black fly caused the transmission of parasite to human body. This study focused on solving the River Blindness disease using the SIR model with vital dynamic.This paper aims to solve the ordinary differential equation (ODE) by using steady state theorem to identify the change percentage of susceptible, infected and recovery for the population in Northern Nigeria, Africa in a time period. The initial percentage of susceptible individual is 0.65 of the population, but only 0.01 of the susceptible individuals are infected with the disease and 0 of them has recovered. The progression of the disease after 90 days is predicted using the Euler Method in Matlab